2014
DOI: 10.1038/mp.2013.192
|View full text |Cite
|
Sign up to set email alerts
|

FGF-21, a novel metabolic regulator, has a robust neuroprotective role and is markedly elevated in neurons by mood stabilizers

Abstract: Fibroblast growth factor-21 (FGF-21) is a new member of the FGF super-family and an important endogenous regulator of glucose and lipid metabolism. It has been proposed as a therapeutic target for diabetes and obesity. Its function in the central nervous system (CNS) remains unknown. Previous studies from our laboratory demonstrated that aging primary neurons are more vulnerable to glutamate-induced excitotoxicity, and that co-treatment with the mood stabilizers lithium and valproic acid (VPA) induces synergis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 41 publications
2
78
0
Order By: Relevance
“…We also demonstrated that activation of the cell survival factor Akt-1 occurs upstream and downstream of FGF-21 and that both protein molecules are involved in the synergistic neuroprotective effects of VPA/lithium cotreatment in aging primary neurons (Leng et al, 2015). Interestingly, treatment of primary neurons with lithium produces small but significant effects on FGF21 expression, while VPA and other related HDAC inhibitors alone are ineffective in inducing FGF21.…”
Section: Introductionmentioning
confidence: 79%
“…We also demonstrated that activation of the cell survival factor Akt-1 occurs upstream and downstream of FGF-21 and that both protein molecules are involved in the synergistic neuroprotective effects of VPA/lithium cotreatment in aging primary neurons (Leng et al, 2015). Interestingly, treatment of primary neurons with lithium produces small but significant effects on FGF21 expression, while VPA and other related HDAC inhibitors alone are ineffective in inducing FGF21.…”
Section: Introductionmentioning
confidence: 79%
“…5C). As a positive control we also tested if FGF21 activated AKT/ERK survival signaling at 37°C as previously reported in neurons (Leng et al, 2015). Paradoxically, AKT/ERK phosphorylation was decreased 24h later potentially suggesting feedback inhibition (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…FGF21 also has a strong neuroprotective role and may act on mood and other cognitive systems [103]. FGF21 appears to modulate circadian behaviors and suppress physical activity through its actions on the central nervous system [104].…”
Section: Modifiers Of Leptinmentioning
confidence: 99%